Analisis Penerapan Kode Etik pada Guru BK - Akhir Pardamean Harahap; Muhammad siddik; Nur hikmah Agustina; Luthvi Hafizah; M. Adrian Syahputra; Annisa Umamy; Zainal Abidin Dalimunthe; Santia Putri Khairuna; Ulfatun Ni'mah; Ahmad Fauzi Nst; Abdul Rahman Srg; Nura'ini; Muhammad Radja; Anis Damayani (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Implementing a code of ethics is a crucial aspect in the Guidance and Counseling (BK) teaching profession, considering their vital role in helping students overcome various personal, social, academic and career problems. This research aims to analyze the implementation of the code of ethics for guidance and counseling teachers in secondary schools, as well as identifying the obstacles and strategies faced in its implementation. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation and documentation.